Plant miRNAs for Improved Gene Regulation in a Wide Range of Human Cancers - Maksym Zoziuk; Vittorio Colizzi; Pavlo Krysenko; Maurizio Mattei; Roberta Bernardini; Fabio Massimo Zanzotto; Stefano Marini; Dmitri Koroliouk (Current Issues in Molecular Biology)
Determining the relationships between miRNA expression, target genes, and cancer development is critical to cancer research. The possibility of correlating miRNA expression with plant or artificial ones provides prerequisites for cancer treatment. Based on the broad database of human miRNA expression for all cancer types, we grade human miRNAs by their expression level. The identified deficient miRNAs are compared with their target genes for coincidences in their expression directions. The replacement of human miRNAs is proposed to be implemented, using plant miRNAs closest to the human-deficient ones. Such plant substitutes are identified by analyzing the average complementarity of all human under-expressed miRNAs. It was established that the number of downregulated miRNAs is almost 2.5 times greater than that of upregulated miRNAs. There is no significant correlation between the expression of miRNA and genes, implying many other expression regulation mechanisms exist. Working on the organization of experimental verification of the obtained statistical studies, we present significant regularities that provide grounds for considering some plant microRNAs as possible means of compensating for insufficient expression of regulatory microRNAs in humans and animals in a wide range of oncological diseases.